(untitled) (Research, Society and Development, 2023)
The aim of this study is to evaluate the use and applicability of Platelet-rich Fibrin (PRF) in surgical procedures of exodontia. The methodology was to perform an integrative literature review that was developed in six phases, in which the guiding question was elaborated by means of the PICo strategy. Thus bibliographic searches were performed in the electronic portals PubMed, LILACS and Cochrane Library, with the keywords Platelet-Rich Fibrin, Extraction and Regeneration, in which 20 articles were selected for the development of this review. he PRF has been increasingly effective in its various applications, especially in soft tissue healing, post-exodontia, contributing to the healing time, morbidity and amount of analgesics needed to reduce pain. Given the above, it is clear that PRF has a high capacity for the stimulation and regeneration of the natural healing process of tissues at extraction sites. Recent findings indicate that PRP can be considered as an efficient, cost-effective and simple therapeutic support for extraction procedures. Furthermore, the use of PRF in surgical procedures for tooth extraction has been shown to be advantageous in terms of tissue healing and bone regeneration, as well as having an expressive role in reducing the risk of delay in the recovery of patients undergoing therapies with oral bisphosphonates. Improvements in the techniques used with PRF can be summed up, as well as further studies and clinical trials with larger samples may confirm the results discussed in this work.